Plasmonic Optical Fibre–Based Point-of-Care Test for Periodontal MIP-1α Detection: A Validation Study of a Multiplexed Biosensor Prototype - Marco Annunziata; Francesco Arcadio; Emanuela Stampone; Debora Bencivenga; Gennaro Cecoro; Chiara Marzano; Angelantonio Piccirillo; Fulvio Della Ragione; Nunzio Cennamo; Luigi Zeni; Adriana Borriello; Luigi Guida (International Dental Journal, 2025)
Introduction: The aim of this study was to assess the analytical performance of a multiplexed plasmonic optical fibre–based point-of-care test (POCT) in detecting and quantifying salivary macrophage inflammatory protein-1 alpha (MIP-1α) by comparing it with a standard enzyme-linked immunosorbent assay (ELISA). Methods: Three plastic optical fibres (POFs) were modified to host a self-assembled monolayer (SAM) of anti-MIP-1α antibodies. Each of them was interposed between a light source and a spectrometer to detect the variations in the refractive index at the POF-SAM interface caused by surface plasmon resonance (SPR) when the antibody-analyte binding occurred. A dose-response Langmuir fitting curve, with MIP-1α dilutions from 0.25 to 10 pM, was calculated. Fifty salivary samples from consecutively enrolled subjects were tested by the SPR-POF biosensor and ELISA, and the obtained values were compared (Spearman’s rank correlation test). Differences in MIP-1α levels among patients based on age, gender and the presence or absence of periodontitis were also analysed (Mann-Whitney U test). Results: A strong positive correlation between SPR-POF and ELISA measurements was found (Spearman’s rs = 0.894, P < .001). The SPR-POF limit of detection (LoD) was 0.15 pM, even lower than the ELISA LoD (0.78 pM). Higher (P < .05) MIP-1α levels in periodontitis compared to non-periodontitis patients were found. Conclusions: The developed 3-arm plasmonic POCT performed comparably to ELISA in detecting and quantifying salivary MIP-1α, both in terms of LoD and accuracy, with measurement rapidity and reliability enhanced by the multiplexed 3-arm design. Clinical Relevance: The novel SPR-POF prototype would be of value for future studies related to POCT devices for monitoring of periodontal health and disease.